Temperature and Plant Genotype Alter Alkaloid Concentrations in Ryegrass Infected with an Epichloë Endophyte and This Affects an Insect Herbivore - Hennessy, Louise M.; Popay, Alison J.; Finch, Sarah C.; Clearwater, Michael J.; Cave, Vanessa M. (Frontiers in Plant Science, 2016)
Asexual Epichloё endophytes colonise agricultural forage grasses in a relationship which is mutually beneficial and provides the host plant with protection against herbivorous insects. The endophyte strain AR37 (Epichloё festucae var. lolii) produces epoxy-janthitrem alkaloids and is the only endophyte known to provide ryegrass with resistance against porina larvae (Wiseana cervinata (Walker)), a major pasture pest in cooler areas of New Zealand. This study examined the effect of temperature on concentrations of epoxy-janthitrems in AR37-infected ryegrass and determined how the resulting variations in concentration affected consumption, growth and survival of porina larvae. Twenty replicate pairs of perennial (Lolium perenne L.) and Italian ryegrass (Lolium multiflorum Lam.) plants with and without endophyte were prepared by cloning, with one of each pair grown at either high (20°C) or low (7°C) temperature. After 10 weeks, herbage on each plant was harvested, divided into leaf and pseudostem, then freeze dried and ground. Leaf and pseudostem material was then incorporated separately into semi-synthetic diets which were fed to porina larvae in a bioassay over 3 weeks. Epoxy-janthitrem concentrations within the plant materials and the semi-synthetic diets were analysed by HPLC. AR37-infected ryegrass grown at high temperature contained high in planta concentrations of epoxy-janthitrem (30.6 µg/g in leaves and 83.9 µg/g in pseudostems) that had a strong anti-feedant effect on porina larvae when incorporated into their diets, reducing their survival by 25-42% on pseudostems. In comparison, in planta epoxy-janthitrem concentrations in AR37-infected ryegrass grown at low temperature were very low (0.67 µg/g in leaves and 7.4 µg/g in pseudostems) resulting in a small anti-feedant effect in perennial but not in Italian ryegrass. Although alkaloid concentrations were greatly reduced by low temperature this reduction did not occur until after 4 weeks of exposure. Alkaloid concentrations were slightly lower in Italian than in perennial ryegrass and concentrations were higher in the pseudostems when compared with the leaves. In conclusion, epoxy-janthitrems expressed by the AR37 endophyte show strong activity against porina larvae. However, when ryegrass plants are grown at a constant low temperature for an extended period of time in planta epoxy-janthitrem concentrations are greatly reduced and are less